Konstitusi dan Perlindungan Hak Kewarganegaraan Ganda : Tantangan dan Solusi di Indonesia - Ahmad Muhamad Mustain Nasoha; Ashfiya Nur Atqiya; Imro’atus Sholikhah; Sri Hafsari Fakriyah; Khansa Naila Nurhusna (Federalisme: Jurnal Kajian Hukum dan Ilmu Komunikasi, 2024)
Dual citizenship presents a multifaceted issue for many nations,including Indonesia,especially in the context of increasing globalization and international mobility.Under Indonesia’s Citizenship Law No.12 of 2006,only single citizenship is recognizet,which poses various legal and administrative challenges for individuals holding dual citizenship.This study investigates the constitutional and human rights issues surrounding dual citizenship in Indonesia,examining the difficulties arising from the country’s single citizenship policy ang exploring potential solutions.The focus is on legal reforms,the implementation of international treaties,and enhanced international cooperation as means to address these challenges.Findings suggest that revising the Citizenship Law,integrating relevant international treaties,and improving public education on dual citizenship could significantly improve rights protection.The study advocates for Indonesia to consider legal reforms and strengthen international collaboration to better manage and fairly address the complexities of dual citizenship.